Effect of reduced irrigation on postharvest quality of pear (Pyrus communis L.) cv. Triumph of Vienna - Vélez-Sánchez , Javier Enrique; Balguera-López, Helber Enrique; Álvarez-Herrera, Javier Giovanni (Revista de Ciencias Agrícolas, 2026)
Pear (Pyrus communis L.) is a fruit species of significant economic importance worldwide. This study focused on reducing irrigation during the rapid growth stage of the pear cv. Triumph of Vienna, specifically during the period of lower rainfall in the Colombian tropics, and on the effect of slight water stress on postharvest behavior. Three irrigation treatments were applied during the 2014 and 2015 growing seasons. One control treatment (T0) was irrigated at 100% of crop evapotranspiration (ETc), and two regulated deficit irrigation (RDI) treatments (T1 and T2) were used. Trees under treatments T1 and T2 were irrigated at 100% ETc, except during the rapid fruit growth phase. During this phenological period, the T1 trees were irrigated at 74% and 48% ETc in 2014 and 2015, respectively, whereas the T2 trees were irrigated at 60% and 27% ETc. Pear fruits were stored at 1 °C and 90% relative humidity. Storage ended after 49 and 59 days for fruits evaluated in 2014 and 2015, respectively. The results showed that deficit irrigation did not alter important postharvest properties of pear, such as firmness, carotenoids, and color. However, titratable acidity, soluble solids, and respiration were more sensitive to deficit irrigation, showing differences compared to pears from well-watered trees and a tendency to accelerate maturation due to the mild stress that RDI can generate in trees. Therefore, in the Colombian tropics, irrigation can be significantly reduced without altering the main postharvest properties of pears.